Honey as an alternative wound healing therapy: a systematic review of clinical and preclinical evidence (2020-2024) - Eni Kusyati; Dwi Indah Iswanti; Sa’adah Mujahidah; Dewi Mayangsari (International Journal of Public Health Science (IJPHS), 2026)
Wound management remains a significant global public health challenge, contributing to substantial morbidity, mortality, and healthcare costs. Honey has been increasingly investigated as a complementary wound care agent due to its antimicrobial, anti-inflammatory, and wound-healing properties. This systematic review aimed to synthesize and critically evaluate the current evidence on the use of honey as an alternative wound treatment. A systematic review was conducted following PRISMA guidelines. Six electronic databases (Scopus, Nature, ProQuest, EBSCO, SpringerLink, and ScienceDirect) were searched using predefined search terms for studies published between 2020 and 2024. Inclusion criteria encompassed human studies, mixed-methods or quantitative designs, and interventions using honey for wound care. Study quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. From 302 initially identified articles, 16 studies met the inclusion criteria after removing duplicates and screening. The included studies comprised randomized controlled trials, prospective controlled studies, case series, and in vitro investigations. Three themes emerged: i) Honey as a wound-healing therapy, demonstrating antimicrobial, anti-inflammatory, and biofilm-inhibiting properties; ii) Benefits of medical-grade honey (MGH), including accelerated epithelialization, reduced infection rates, and shorter recovery times; and iii) Recommendations for honey as a cost-effective, accessible alternative treatment. The evidence supports honey as a promising adjunctive therapy for wound management, particularly in resource-limited settings. However, the heterogeneity in study designs, honey types, and wound categories limits definitive conclusions. Future large-scale randomized controlled trials with standardized outcomes are needed to establish clinical guidelines for honey-based wound care.